Using expert knowledge and modeling to define mangrove composition, functioning, and threats and estimate time frame for recovery - Mukherjee, Nibedita (Blackwell Publishing Ltd, 2014)
Mangroves are threatened worldwide, and their loss or degradation could impact functioning of the ecosystem. Our aim was to investigate three aspects of mangroves at a global scale: (1) their constituents (2) their indispensable ecological functions, and (3) the maintenance of their constituents and functions in degraded mangroves. We focused on answering two questions: “What is a mangrove ecosystem” and “How vulnerable are mangrove ecosystems to different impacts”? We invited 106 mangrove experts globally to participate in a survey based on the Delphi technique and provide inputs on the three aspects. The outputs from the Delphi technique for the third aspect, i.e. maintenance of constituents and functions were incorporated in a modeling approach to simulate the time frame for recovery. Presented here for the first time are the consensus definition of the mangrove ecosystem and the list of mangrove plant species. In this study, experts considered even monospecific (tree) stands to be a mangrove ecosystem as long as there was adequate tidal exchange, propagule dispersal, and faunal interactions. We provide a ranking of the important ecological functions, faunal groups, and impacts on mangroves. Degradation due to development was identified as having the largest impact on mangroves globally in terms of spatial scale, intensity, and time needed for restoration. The results indicate that mangroves are ecologically unique even though they may be species poor (from the vegetation perspective). The consensus list of mangrove species and the ranking of the mangrove ecological functions could be a useful tool for restoration and management of mangroves. While there is ample literature on the destruction of mangroves due to aquaculture in the past decade, this study clearly shows that more attention must go to avoiding and mitigating mangrove loss due to coastal development (such as building of roads, ports, or harbors).